Rotavirus and other enteropathogens in childhood acute diarrhoea: a study of two centres in Malaysia - Lee, W.S.; Rajasekaran, G.; Pee, S.; Karunakaran, R.; Hassan, Hamimah; Puthucheary, S.D. (Wiley, 2006)
AIM: To study the role of rotavirus in children hospitalised for acute gastroenteritis (AGE) in two urban hospitals in Malaysia. METHODS: A 12-month prospective study (January to December 2002), in children younger than 14 years with AGE hospitalised to the paediatric units of University of Malaya Medical Centre (UMMC), Kuala Lumpur; and Hospital Sultanah Aminah (HSA), Johor Bahru, Malaysia was conducted. RESULTS: In 2002, 399 and 1307 children with AGE were admitted to UMMC and HSA, respectively. Two hundred and eighty-eight (72) stool samples from UMMC and 901 (69) samples from HSA were analysed. Rotavirus was the most common aetiological agent identified in both centres (average 32; UMMC 35, HSA 30, P = 0.94). The peak age group for rotavirus-related hospitalisation was 24-35 months for UMMC and 12-23 months for HSA. Nine percent of patients hospitalised for rotavirus infection in UMMC and 22 of patients in HSA were older than 5 years of age. An outbreak of rotavirus infection within the communities served by both centres resulting in an increase in hospital admissions of rotavirus gastroenteritis was observed in both units from January to March 2002. CONCLUSION: The peak age group for rotavirus-related hospital admission in this study was much older, between 12 to 35 months. It is uncertain whether this was related to the outbreak of rotavirus gastroenteritis observed within two urban areas from January to March 2002 causing re-infection with rotavirus in older children.